Awareness of African Horse Sickness as an Emerging Arbovirus Disease - Atik Ratnawati; Muharam Saepullah; Indrawati Sendow; NLP Indi Dharmayanti (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2018)
African horse sickness (AHS) is one of the important arbovirus diseases in horse. The disease is fatal and should be transmitted by vector. This disease is potential to spread rapidly and has impacts in public health and socio-economic, especially in the international trade of horses and its products. The paper describes AHS, some factors that influence the disease, how to control the disease and its current situation in Indonesia. African horse sickness has been declared as notifiable disease in OIE list, therefore, the disease becomes strategic in the country that has high horse population. Climate changes affect vector population and spreading of the disease. In order to anticipate the entering of AHS infection in Indonesia, the government needs to facilitate the research on horse diseases including the safe laboratory facilities to handle exotic diseases and provide diagnostic tool for early detection.